4n-3=2(n-1)-1

Simple and best practice solution for 4n-3=2(n-1)-1 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4n-3=2(n-1)-1 equation:


Simplifying
4n + -3 = 2(n + -1) + -1

Reorder the terms:
-3 + 4n = 2(n + -1) + -1

Reorder the terms:
-3 + 4n = 2(-1 + n) + -1
-3 + 4n = (-1 * 2 + n * 2) + -1
-3 + 4n = (-2 + 2n) + -1

Reorder the terms:
-3 + 4n = -2 + -1 + 2n

Combine like terms: -2 + -1 = -3
-3 + 4n = -3 + 2n

Add '3' to each side of the equation.
-3 + 3 + 4n = -3 + 3 + 2n

Combine like terms: -3 + 3 = 0
0 + 4n = -3 + 3 + 2n
4n = -3 + 3 + 2n

Combine like terms: -3 + 3 = 0
4n = 0 + 2n
4n = 2n

Solving
4n = 2n

Solving for variable 'n'.

Move all terms containing n to the left, all other terms to the right.

Add '-2n' to each side of the equation.
4n + -2n = 2n + -2n

Combine like terms: 4n + -2n = 2n
2n = 2n + -2n

Combine like terms: 2n + -2n = 0
2n = 0

Divide each side by '2'.
n = 0

Simplifying
n = 0

See similar equations:

| (11-9)3power*2= | | (11-9)16*2= | | (11-9)3*2= | | 85-(15-3x)=141-11 | | 2x+144=358 | | 124-2x=12 | | 3u-9=-6(u-9) | | 0.3=0.30 | | 6(v-6)-8v=-26 | | 9/z=18/42 | | 10/2+12/2x3 | | 2a+2c= | | 3x+50x=180 | | cos(10x)+cos(3x)=0 | | -x+11=5x+12(7x-2) | | 10-8x=51-15x | | 4x+31=13x-15 | | 2x^2-36x=1 | | 6x-1/3=x/4+3/6 | | (x+19)=0 | | x^7=9x | | 4x+28=44 | | x^2+1/x^2 | | 10x=18xy | | 6a+5a-3a= | | 2(2x-y)=2(x+y)-4 | | 6x(x-4)+2(x-4)=0 | | 2w^2+19w+53=(w+7) | | 4x+8=x+10 | | -x^2+4x+32=0 | | -2x^2+10x+100=0 | | -x^3+9x^2+22x=0 |

Equations solver categories